Development of interactive multimedia articulate storyline to improve elementary school students' learning outcomes regarding the history of the formulation of Pancasila - Siti Nur Hidayatur Rofi'ah; Susilo Tri Widodo (Universitas Muhammadiyah Malang, 2024)
The low student learning outcomes on the history of the formulation of Pancasila and the learning media used by teachers are less creative and innovative, causing students to feel bored and less active in learning, this is the background of researchers in conducting research. The purpose of this study was to develop, test the feasibility, and test the effectiveness of Articulate Storyline interactive multimedia in improving the learning outcomes of Pancasila formulation history material for fourth-grade students of SDN Gondoriyo Semarang City. Researchers use development research or Research and Development (R&D) with the Borg and Gall development model. Researchers used observation, interviews, documentation, questionnaires, and tests as data collection techniques. Researchers used data analysis techniques of normality test, t-test, and N-Gain test. The results of the material expert feasibility assessment obtained a score of 85.8%, and the media expert assessment obtained a score of 86.25%. The validation results of material experts and media experts show that the interactive multimedia articulate storyline is